Psoriasis and its association with serum lipid profile: A hospital-based case-control study - Pokhrel, Kumar; Shahi, Kamal Jung; Parajuli, Sudip (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Psoriasis is a chronic immune-mediated inflammatory dermatosis associated with significant cardiovascular comorbidity. Population-specific data on lipid abnormalities in Nepalese psoriasis patients are limited. This study aimed to determine the association of psoriasis with serum lipid profiles. Methods: This hospital-based case-control study enrolled 73 confirmed psoriasis cases and 73 age and sex-matched healthy controls. Fasting serum triglycerides, total cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol were measured. Disease severity was graded by the Psoriasis Area and Severity Index. Results: Psoriasis vulgaris was the commonest clinical pattern 40 (54.8%). Cases had significantly elevated median triglycerides (145.0 vs. 122.0 mg/dl; p<0.001) and very low-density lipoprotein cholesterol (37.0 vs. 21.0 mg/dl; p<0.001), and significantly lower high-density lipoprotein cholesterol (60.40 vs. 72.73 mg/dl; p<0.001) and low-density lipoprotein cholesterol (p<0.001). Total cholesterol did not differ significantly (p=0.703). Elevated very low-density lipoprotein cholesterol (odds ratio [OR] 9.06; p<0.001), low high-density lipoprotein cholesterol (OR 6.30; p=0.017), and hypertriglyceridemia (OR 3.03; p=0.003) were more prevalent among cases. No significant correlation was found between Psoriasis Area Severity Index and lipid parameters. Conclusions: Psoriasis is associated with a proatherogenic lipid profile. Routine fasting lipid profiling at diagnosis is recommended for early cardiovascular risk assessment.